(untitled) (Thành phố Hồ Chí Minh, 2014)
Contents: Question types; talks and announcements; converations; academic talks and discussions; practice tests; scripts.
Keywords: English language,English language,Anh ngữ; Examinations,Listening,Kỳ thi